World Christianity, urbanization, and identity - Biney, Moses O.; Ngwa, Kenneth Numfor; Barreto, Raimundo (World Christianity and Public Religion, 2021)
World Christianity, Urbanization and Identity argues that urban centers do not only offer places for persons to live, shop, and seek entertainment, but deeply shape people's ethics, behavior, sense of justice, and how they learn to become human. Given that religious participation and institutions are vital to individual and communal life, particularly in urban centers, this interdisciplinary volume provides insights into the interaction between urban change and religious formation in the word today